Tyrosol 1, 2, 3-triazole analogues as new acetylcholinesterase (AChE) inhibitors. (October 2020) - Bousada, Guilherme M.; de Sousa, Bianca L.; Furlani, Gabriela; Agrizzi, Ana Paula; Ferreira, Priscila G.; Leite, João Paulo V.; Mendes, Tiago Antônio de O.; Varejão, Eduardo V.V.; Pilau, Eduardo J.; dos Santos, Marcelo H.
Graphical abstract: Highlights: Tyrosol derivatives and 1, 2, 3-triazoles are potential acetylcholinesterase inhibitors Derived from 4-methylumbelliferone (30 ) showed an IC50 value of 14.66 ± 2.29 μmol L −1 Kinetic study and computational simulation suggested competitive inhibition mechanism High potential prototypes for the development of new acetylcholinesterase inhibitors Development of new drugs and pesticides, including for managing Alzheimer's disease Abstract: The present work proposed the preparation of triazolic analogues of tyrosol, a biophenol found in olive oil and whose wide range of bioactivities has been the target of many studies. We obtained fifteen novel tyrosol derivatives and the compounds of the series were later evaluated as acetylcholinesterase (AChE) inhibitors. The study of AChE inhibition is important for the development of new drugs and pesticides, and especially the research for managing Alzheimer's disease. The most active compound, namely 7-({1-[2-(4-hydroxyphenyl)ethyl]-1 H -1, 2, 3-triazol-4-yl}methoxy)-4-methyl-2 H -chromen-2-one (30 ), showed IC50 value of 14.66 ± 2.29 μmol L −1 . Docking experiments corroborated by kinetic assay are suggestive of a competitive inhibition mechanism. Derivatives interacted with amino acids from the AChE active site associated to the development of Alzheimer's disease. The results indicate that the compounds synthesized have a high potential as prototypes for the development of new acetylcholinesterase inhibitors.